2019
DOI: 10.1002/mop.32215
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensing scheme based on fiber ring microwave photonic filter with erbium doped fiber amplification

Abstract: The temperature sensing scheme based on fiber ring microwave photonic filter (MPF) with erbium doped fiber amplification (EDFA) is proposed and experimentally demonstrated. The fiber ring is used as the time delay element, as well as a sensing element, and by introducing an EDFA to compensate the loss in the fiber ring, the number of the effective sampling taps and thus the suppression ratio are increased. When the EDFA power is set at 0.74 mW, the 3 dB bandwidth of the passband and suppression ratio of the MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The peak frequency of the italicjth passband ƒj can be expressed as: 13 ƒj=j×italicFSR=j×cnL,j=1,2,3. When temperature changes, the frequency shift of the j th passband can be derived as: {right left}trueΔfj=j×ΔFSR=j×cnl+Δn+nlcnl+l=j×cl'Δnnl+Δn+nlnl+l=fj×l'Δn[]italicnl+()normalΔn+nl, where l is length of the sensing fiber, l is the length of the cavity except the sensing fiber. normalΔn is thermo‐optic effect induce refractive index changes, and it should be noted that here only the thermo‐optic effect is taken into account, because the coefficient of thermal expansion is small enough compared to the thermo‐optic coefficient for neglecting.…”
Section: Experimental Setup and Operation Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The peak frequency of the italicjth passband ƒj can be expressed as: 13 ƒj=j×italicFSR=j×cnL,j=1,2,3. When temperature changes, the frequency shift of the j th passband can be derived as: {right left}trueΔfj=j×ΔFSR=j×cnl+Δn+nlcnl+l=j×cl'Δnnl+Δn+nlnl+l=fj×l'Δn[]italicnl+()normalΔn+nl, where l is length of the sensing fiber, l is the length of the cavity except the sensing fiber. normalΔn is thermo‐optic effect induce refractive index changes, and it should be noted that here only the thermo‐optic effect is taken into account, because the coefficient of thermal expansion is small enough compared to the thermo‐optic coefficient for neglecting.…”
Section: Experimental Setup and Operation Principlesmentioning
confidence: 99%
“…With the rapid development of microwave photonics technology, it has been employed in the sensing systems due to the advantages of low cost, high sensitivity, and easy implementation 12 . Yang et al have proposed a temperature sensing scheme based on a fiber ring microwave photonics filter (MPF) with EDF amplification, and the sensitivity is 11.74 kHz/°C when the passband at 1.6 GHz is adopted for temperature monitoring 13 . Huang et al have proposed a microwave interrogated sapphire fiber Michelson interferometer for high‐temperature sensing, and the sensor shows a good sensitivity in the temperature range of 100 ~ 1400°C 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martin-Vela et al reported an inclinometer based on a fiber ring laser [ 29 ], where a thin core fiber modal interferometer worked as a filter for the system. Moreover, Fu reported a temperature sensing system based on a fiber ring microwave photonic filter (MPF) [ 30 ], which combined microwave photonics with a fiber ring laser. Mateusz proposed a FRL sensor which can simultaneously measure temperature and humidity [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber optic sensors have the advantages of high sensitivity, compact structure, anti-electromagnetic interference, and remote control, [1][2][3] which are increasingly applied to the detections of basic physical parameters, such as temperature, [4][5][6] transverse load, 7,8 refractive index, [9][10][11] and strain. [12][13][14] With the development of science and technology, multi-parameter detections have become a hot topic in recent years, for instance, integrated optic-fiber sensor based on enclosed EFPI and structural phase-shift for discriminating measurement of temperature, pressure and RI temperature and refractive index, 15 transverse load and refractive index fiber sensor based on photonic crystal fiber, 16 a sawtooth stressor-assisted highly birefringent fiber Bragg grating for temperature and strain measurement.…”
Section: Introductionmentioning
confidence: 99%